Review of the occurrence and structural controls of Baryte resources of Nigeria - N A Labe; P O Ogunleye; A A Ibrahim; T Fajulugbe; S T Gbadema (Brawijaya University, 2018)
Baryte occurrences in Nigeria are spread across the Cretaceous Benue Trough which comprises of carbonaceous shales, limestone, siltstones, sandstones as well as in the northeastern, northwestern and southeastern parts of the Precambrian Basement Complex comprising of metasediments and granitoids. The mineralization is structurally controlled by NW-SE, N-S and NE-SW fractures. The common mode of occurrence for these barytes is the vein and cavity deposits type usually associated with galena, sphalerite, copper sulphide, fluorite, quartz, iron oxide as gangue minerals. Principal areas of baryte occurrences in Nigeria include Nassarawa, Plateau, Taraba, Benue, Adamawa, Cross River, Gombe, Ebonyi, and Zamfara. A large part of the vast baryte resources in Nigeria is still underexploited and further exploration work is needed to boost its exploitation. The inferred resource and proven reserve of baryte is put at over 21,000,000 and about 11,000,000 metric tons respectively. The economic evaluation of these barytes is viable having low (SG = < 3.5) to high (SG = 5.3) grades. The presence of associated minerals produces low quality barytes and as such blending and beneficiation is required to improve its quality.